2011
DOI: 10.1152/jn.00739.2010
|View full text |Cite
|
Sign up to set email alerts
|

Evoked potentials in large-scale cortical networks elicited by TMS of the visual cortex

Abstract: Single pulses of transcranial magnetic stimulation (TMS) result in distal and long-lasting oscillations, a finding directly challenging the virtual lesion hypothesis. Previous research supporting this finding has primarily come from stimulation of the motor cortex. We have used single-pulse TMS with simultaneous EEG to target seven brain regions, six of which belong to the visual system [left and right primary visual area V1, motion-sensitive human middle temporal cortex, and a ventral temporal region], as det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 70 publications
6
28
0
Order By: Relevance
“…Our results on the influence of TMS on the resting state connectivity between separate brain regions extend previous research on the topic of distant aftereffects of TMS (Bestmann et al 2008;Chouinard et al 2003;Fox et al 2012;Garcia et al 2011;Hampson and Hoffman 2010;Ruff et al 2009;Zanto et al 2011). Previous research has shown that using conditioning pulses over distant areas such as the motion sensitive area MT (Pascual-Leone and Walsh 2001), parietal cortex (Silvanto et al 2009), or frontal eye fields (Silvanto et al 2006) can affect the propensity of a subsequent pulse over the occipital cortex to elicit phosphenes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results on the influence of TMS on the resting state connectivity between separate brain regions extend previous research on the topic of distant aftereffects of TMS (Bestmann et al 2008;Chouinard et al 2003;Fox et al 2012;Garcia et al 2011;Hampson and Hoffman 2010;Ruff et al 2009;Zanto et al 2011). Previous research has shown that using conditioning pulses over distant areas such as the motion sensitive area MT (Pascual-Leone and Walsh 2001), parietal cortex (Silvanto et al 2009), or frontal eye fields (Silvanto et al 2006) can affect the propensity of a subsequent pulse over the occipital cortex to elicit phosphenes.…”
Section: Discussionsupporting
confidence: 89%
“…Such a possibility is in line with a number of recent studies that have demonstrated that the effect of TMS extends beyond the focus of stimulation, often to remote regions that are anatomically connected to the focal region (Bestmann et al 2008;Chouinard et al 2003;Fox et al 2012;Garcia et al 2011;Hampson and Hoffman 2010;Ruff et al 2009;Zanto et al 2011). …”
supporting
confidence: 58%
“…Compelling evidence has also been found in the visual system. Garcia et al (2011) applied TMS to different areas of the visual system, including the left and right primary visual area, middle temporal cortex, and a ventral temporal region. Interestingly, both site-specific and site-invariant EEG responses were obtained.…”
Section: Cortico-cortical Connectivity From Nodes To Brain Hubsmentioning
confidence: 99%
“…At first, different nodes (site-specific responses) and eventually the same hubs are activated (site-invariant responses). The figure simulates results fromGarcia et al (2011). (For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.…”
mentioning
confidence: 99%
“…For example, single-pulse TMS to the motor cortex produces immediate EEG changes in the region under the TMS coil, which spread over a few milliseconds to ipsilateral motor, premotor and parietal regions, and then several milliseconds later to the contralateral motor cortex (Ilmoniemi et al 1997; Komssi et al 2002). In one recent study, stimulation of different regions within visual cortex resulted in widespread, long-lasting oscillations, with the precise pattern of network activations containing both stimulation site-specific and site-invariant features (Garcia et al 2011). Similarly, a number of studies have demonstrated that rTMS produces alterations in activity in distributed networks.…”
Section: Introductionmentioning
confidence: 99%